(untitled) (Research, Society and Development, 2024)
Introduction: The treatment of teeth with pulpal necrosis and incomplete root development presents a challenge in endodontic practice due to the fragility of the root walls and open apices. Techniques such as apexogenesis, apicoectomy, and pulp regeneration are treatment options for teeth with incomplete root development and pulp alterations, with pulp regeneration being a promising alternative. Objective: This study aims to evaluate the current knowledge on pulp revascularization and its success in endodontic practice. Methodology: A literature review was conducted by searching for studies in the following databases: PubMed, SciELO, Virtual Health Library (VHL), and ScienceDirect. The search included articles in English and Portuguese published between 2018 and 2024. Inclusion criteria consisted of case reports, clinical research, experimental research articles, and literature reviews available in full text. Exclusion criteria included abstracts, conference proceedings, dissertations, monographs, theses, and books that were not relevant to the topic. Results: After applying the criteria, 15 articles were selected for the study, with most of the included articles presenting a comparison between apicoectomy and pulp revascularization. Conclusion: It can be concluded that this treatment is viable in cases of incomplete root development; however, further studies are needed to standardize a single protocol to achieve effective clinical outcomes.